A discussion on the genus Fomitiporella (Hymenochaetaceae, Hymenochaetales) and first record of F. americana from southern South America - Pildain, María Belén (2018)
Fomitiporella has traditionally been delimited based on the gross morphology of the basidiomes, hyphal structure and basdiospores. Recently, phylogenetic studies supported the incorporation of an extensive number of species within the genus. Although most of its species are nested in the ‘Phellinotus clade’ (Hymenochaetaceae, Basidiomycota), genera such as Arambarria, Inocutis and Phellinotus were not included in previous analysis. To further our understanding of the genus, new sequences from 28S and ITS nuc rDNA genes were jointly analysed with a large selection of taxa in the ‘Phellinotus clade’, also with re-examination of morphological and ecological data. Results showed several lineages in what has hitherto been considered to represent Fomitiporella, indicating that the genus is paraphyletic as presently circumscribed. There is a well-supported Fomitiporella core group that includes the type species and nine other monophyletic lineages with high support, of which those representing Arambarria, Inocutis and Phellinotus are distinct from the Fomitiporella core group by macro and micromorphological traits and/ or biogeographic distribution. Fomitiporella americana, a species described from SE USA, was found in the Patagonian forests of southern Argentina and Chile; it is the taxon responsible for the white heart-rot found on standing Austrocedrus chilensis and one of the taxa decaying wooden tiles of historic churches in Chiloé Is., Chile.